Answers

2014-08-08T07:53:01+08:00
The rate of A is X/60; where X is the total distance travelled. After 20 seconds, they met. This means, combining their distances, they have travelled the whole track in 20 seconds. So, we have the equation: X = (X/60)(20) + Y --> X = (X/3) + Y --> X is the Total Distance, (X/3) is A's distance after 20 seconds and Y is the distance of B after 20 seconds. Since there is no distance given, we solve the distance traveled by B in terms of X: (3/3)X - (1/3)X = Y --> (2/3)X = Y. We now divide the distance by 20 seconds to know the rate of B: B = (2/3)X / 20 --> B = X/30. This means B can run around the track in 30 seconds.
0